(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
The paper aims to investigate the possibility of an invasive method for electrical capacitance tomography system for steel pipe application. This work presents the development process for modeling an ECT (Electrical Capacitance Tomography) sensor using COMSOL Multiphysics. COMSOL Multiphysics software is implemented as the main tool to model the ECT system. The 12 electrodes are modeled in 2-dimensional and it is based on the invasive approach. The ECT system is developed to obtain the electrical potential distribution between electrodes when an electric field is applied. Besides, it also obtains the permittivity distribution inside the closed pipe. This invasive approach is applied for the steel pipe that cannot be used with common ECT. Several positions of bubble air as the obstacle in the oil medium are tested. As a result, the sensor readings performance inside the region of interest is analyzed. Simultaneously, the tomograms are also obtained and analyzed using MATLAB software. A linear back-projection algorithm is implemented to reconstruct the image of the region of interest. Thus, the possibility of the ECT system applied for steel pipe can be observed and compared when there is a change of readings between the full oil and the existing obstacle inside the steel pipe. Besides, the tomograms for each condition tested can be observed. In short, the invasive approach for ECT is seen to be possible to apply for oil-gas application in steel pipe. The LBP algorithm with the average MSSIM value around 0.3 was able to detect the oil-gas regime inside the steel pipe.